2004
DOI: 10.1182/blood-2003-10-3551
|View full text |Cite
|
Sign up to set email alerts
|

Atypical features of familial hemophagocytic lymphohistiocytosis

Abstract: Familial hemophagocytic lymphohistiocytosis (FHLH) is a rare, rapidly progressive disorder of early childhood characterized by uncontrolled activation of T cells and macrophages. Although perforin gene mutations have been described in a proportion of patients with FHLH, the genotype/ phenotype correlation is still limited. Only a few patients with late onset clinical manifestations have been reported. The biochemical and immunologic alterations in the asymptomatic phase are not well known. We report on a famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
61
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 16 publications
4
61
0
Order By: Relevance
“…Although certain perforin mutations may not allow for antibody reactivity, functional analysis of both subjects also demonstrated no significant NK-cell cytotoxicity, indicating that the compound heterozygous mutations result in nonexpressed or nonfunctional perforin. Similar to Busiello et al, 13 there were also phenotypic differences between each affected triplet in our study, including time of onset of disease, as well as differences in the percentage of circulating NK cells, and expression of cellular granzymes A and B. These results suggest that, despite having the same genetic mutations, there are significant polygenetic influences in the development of HLH.…”
Section: Case Report Bsupporting
confidence: 76%
See 3 more Smart Citations
“…Although certain perforin mutations may not allow for antibody reactivity, functional analysis of both subjects also demonstrated no significant NK-cell cytotoxicity, indicating that the compound heterozygous mutations result in nonexpressed or nonfunctional perforin. Similar to Busiello et al, 13 there were also phenotypic differences between each affected triplet in our study, including time of onset of disease, as well as differences in the percentage of circulating NK cells, and expression of cellular granzymes A and B. These results suggest that, despite having the same genetic mutations, there are significant polygenetic influences in the development of HLH.…”
Section: Case Report Bsupporting
confidence: 76%
“…There have been 2 previous reports of perforin gene mutations in twins. 13,14 Twins reported by Lipton et al 14 presented in the newborn period with symptoms consistent with HLH. Genetic analysis demonstrated a single missense mutation in the perforin gene (PRF1) in only one of the twins and their mother.…”
Section: Case Report Bmentioning
confidence: 99%
See 2 more Smart Citations
“…The logjam was broken when Towne and colleagues showed that all 3 IL-36 agonists and IL-36Ra need to be processed at one particular position (with apparently zero tolerance), close to the N-terminus of the precursor protein. 6 Once supplied to cells that have IL-36 receptors in this "polished" form, the vast functional discrepancy disappears between IL-36 and IL-1. What we still do not know is which proteases in nature can "polish" IL-36.…”
mentioning
confidence: 99%